2016
DOI: 10.1097/ta.0000000000000954
|View full text |Cite
|
Sign up to set email alerts
|

Elevated admission international normalized ratio strongly predicts mortality in victims of abusive head trauma

Abstract: Prognostic and epidemiologic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 50 publications
(73 reference statements)
1
18
0
Order By: Relevance
“…This agrees to some extent with the findings of other studies, which reported that higher FFP‐to‐RBC ratios had little or no association with mortality . When considering laboratory results, there were differences observed between the three groups of patients; however, only the first platelet count and aPTT were independently associated with increased risk of in‐hospital mortality, consistent with findings reported previously .…”
Section: Discussionsupporting
confidence: 91%
“…This agrees to some extent with the findings of other studies, which reported that higher FFP‐to‐RBC ratios had little or no association with mortality . When considering laboratory results, there were differences observed between the three groups of patients; however, only the first platelet count and aPTT were independently associated with increased risk of in‐hospital mortality, consistent with findings reported previously .…”
Section: Discussionsupporting
confidence: 91%
“…The presence of elevated INR on admission laboratory testing was also associated with development of DVT later in the hospital stay. Previous work has determined that elevated admission INR is associated with mortality and disability in injured children. However, INR seems to serve more as a marker of poor outcome as opposed to an indicator of bleeding risk or clinical coagulopathy after trauma, and research suggests a treatment target upstream of INR .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of DVT in an ICU population using a screening protocol was 8.9%. The severe TBI treatment bun- Previous work has determined that elevated admission INR is associated with mortality 19,21,[33][34][35] and disability [36][37][38] in injured children. Treatment of DVT with anticoagulant therapy is commonly recommended in order to prevent clot propagation/embolization and longterm morbidity from PTS.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative elevated INR had been con rmed to increase bleeding, complication and mortality in some diseases [11][12][13][14][15][16][17]. Measuring INR before joint surgery was a standard pattern in our institution.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies agreed that high INR values have a strong association with the risk of bleeding [14,15]. A retrospective study found patients with INR≥1.3 had a higher transfusion rate in victims of abusive head trauma [16]. An elevated INR is also associated with increased complications after hand surgery [17].…”
Section: Introductionmentioning
confidence: 94%